The Influence of Digital Transformation, Competence, and Work Discipline on Employee Performance at the Public Works and Spatial Planning Office of Selayar Islands Regency - Amri Muammar; Muhammad Rusydi; Andi Jam’an (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The Influence of Digital Transformation, Competence, and Work Discipline on Employee Performance at the Department of Public Works and Spatial Planning of Kepulauan Selayar Regency, Master’s Thesis, Master of Management Program, Graduate School, Universitas Muhammadiyah Makassar, supervised by Supervisor I Muhammad Rusydi, and Supervisor II Andi Jam’an. This study aims to analyze and explain the Influence of Digital Transformation, Competence, and Work Discipline on Employee Performance at the Public Works and Spatial Planning Office of Selayar Islands Regency. This type of research uses a quantitative method, which is research based on data that can be calculated to produce a solid assessment using SPSS. This study used 65 respondents using multiple linear regression analysis techniques . The results of the study showed that Digital Transformation had a positive and significant effect on employee performance with P = 0.004 < 0.05 with a coefficient value of 3.289. Competency has a positive and significant effect on employee performance with P = 0.014 < 0.05 with a coefficient value of 2.251. Work Discipline has a positive and significant effect on employee performance with P = <0.001 < 0.05 with a coefficient value of 4.381. The Work Discipline variable is the most dominant variable that affects the Performance of Employees of the Public Works and Spatial Planning Office of the Selayar Islands Regency.